2012
DOI: 10.1007/s00429-012-0406-5
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic innervation and serotonin receptor expression of NPY-producing neurons in the rat lateral and basolateral amygdaloid nuclei

Abstract: Pharmacobehavioral studies in experimental animals, and imaging studies in humans, indicate that serotonergic transmission in the amygdala plays a key role in emotional processing, especially for anxiety-related stimuli. The lateral and basolateral amygdaloid nuclei receive a dense serotonergic innervation in all species studied to date. We investigated interrelations between serotonergic afferents and neuropeptide Y (NPY)-producing neurons, which are a subpopulation of inhibitory interneurons in the rat later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 92 publications
3
50
0
1
Order By: Relevance
“…In rats the amygdala receives dense and topographically organized serotonergic inputs from the raphe nucleus, with the BLA showing the highest density of 5-HT terminal innervation (Vertes et al, 1999, Muller et al, 2007, Bonn et al, 2013, Linley et al, 2017). The amygdala also shows moderate to high levels of ligand binding for multiple 5-HT receptor subtypes, including 5-HT 1A, 1B, 2A, 2C,3 and 5-HT 7 receptors (Gustafson et al, 1996, Saha et al, 2010, Bombardi, 2011, Bocchio et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats the amygdala receives dense and topographically organized serotonergic inputs from the raphe nucleus, with the BLA showing the highest density of 5-HT terminal innervation (Vertes et al, 1999, Muller et al, 2007, Bonn et al, 2013, Linley et al, 2017). The amygdala also shows moderate to high levels of ligand binding for multiple 5-HT receptor subtypes, including 5-HT 1A, 1B, 2A, 2C,3 and 5-HT 7 receptors (Gustafson et al, 1996, Saha et al, 2010, Bombardi, 2011, Bocchio et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this study application of 8-OH DPAT induced a slight yet non-significant increase of amplitude of eEPSCs. This effect may be due to an indirect activation of 5-HT 1A receptors located on NPY-expressing GABAergic interneurons (Bonn et al, 2013). Activation of 5-HT 1A receptors could in turn hyperpolarize GABA interneurons and lead to disinhibition of glutamate release.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular serotonin levels in downstream DRN targets, like the basolateral amygdala (BLA), can remain elevated for at least an hour after learning is completed [14,15]. Although serotonin acts through several receptor subtypes in the BLA, the serotonin 2c receptor (5-HT2CR) is of interest because these receptors are heavily expressed in BLA neurons that regulate anxiety [16] and 5-HT2CR agonists promote anxiety in humans [17]. Furthermore, viral-mediated overexpression of 5-HT2CR in amygdala produces anxiogenic effects [18] while pharmacological blockade of amygdala 5-HT2CR prevents stress-induced anxiety-like behaviors [19].…”
Section: Introductionmentioning
confidence: 99%
“…8 H ). Thus, pc-nNOS cells are hyperpolarized by 5-HT via 5-HT1A receptors, in line with the expression of 5-HT1A mRNA in NPY + BLA neurons (Bonn et al, 2013). …”
Section: Resultsmentioning
confidence: 70%
“…However, recent in situ hybridization data have shown that BLA NPY + cells, some of which are thought to be nNOS + (McDonald et al, 1993), can also express inhibitory 5-HT1A receptors (Bonn et al, 2013), suggesting that 5-HT could also hyperpolarize some GABAergic cells. Defining the diversity of 5-HT actions on BLA neuron types is crucial if we are to understand the cellular dynamics occurring in the BLA across different brain states.…”
Section: Introductionmentioning
confidence: 99%